Hormone Therapy and Homocysteine Levels In Postmenopausal Women: A Review of The Literature - Hakan Kıran; Mustafa Kaplanoğlu (Medical Network, 2007)
Homocysteine, a sulfur-containing amino acid is formed during the metabolism (remethylation or transsulfuration) of the essential amino acid methionine. An elevated homocysteine level is important and independent risk factor for cardiovascular disease in postmenopausal women. Homocysteine levels are lower in women compared with men. On the other hand, homocysteine levels is lower during pregnancy and higher during menopause. The determinants of serum homocysteine in healthy postmenopausal women are uncertain. Endogenous estrogens and not androgens are related to serum homocysteine values in postmenopausal women. The mechanism behind this observation remains unclear. The millions of postmenopausal women currently receive estrogen treatment. Estrogen replacement relieves menopausal symptoms such as hot flashes and vaginal atrophy and prevents osteoporosis. Elevations in circulating homocysteine levels also predict a significantly greater risk of coronary artery disease. The underlying mechanism for the pathogenic response is still unclear.